The Goals of Medicine: Debate and Disagreements Around Contraceptive Side Effects - Prince, Ilvie (Kennedy Institute of Ethics journal, 2023)
Since the invention of hormonal contraceptives, there has been disagreement between users and providers about the existence of side effects and their implications for care. The lack of consideration for cisgender women, and other people who may become pregnant, has often been explained by sexist bias in the philosophy of medicine. My goal is to contribute additional elements to this discussion. I will argue that there are structurally embedded assumptions about the responsibilities and goals of medicine that open the door to this sexism in the first place. While we tend to accept that contraception is part of medicine for pragmatic reasons, we do not exhibit the same form of pragmatism when it comes to dealing with side effects. This is an unjustified double standard that fails to recognize the goals of contraception and the fact that it relies on medical expertise to achieve them.